The Self-Awareness and Social Skills of Pediatric Cancer - Oresti, Syalvia; Elengoe, Asita (RRZ Scientific Publishing, 2024)
Children with cancer face significant psychosocial challenges, including emotional distress, social isolation, and impaired self-awareness. These difficulties can impact their treatment adherence, quality of life, and long-term well-being. This study aimed to investigate the levels of self-awareness and social skills among children with cancer in West Sumatra, Indonesia, and explore supportive interventions for these children and their families. A cross-sectional quantitative study was conducted in March 2024 at Childhood Cancer Care West Sumatra. The sample comprised 63 children selected using Accidental Sampling Technique. Data on self-awareness and social skills were collected through validated instruments. The findings revealed that 50.8% of the children exhibited the highest level of self-awareness, while 60.3% demonstrated the highest level of social skills. These findings highlight the importance of addressing the psychosocial needs of children with cancer. Comprehensive support programs should be implemented to enhance their self-awareness, social skills, and emotional well-being. These programs should involve multidisciplinary teams, including psychologists, social workers, and child life specialists, to provide individualized support for children and their families.